The determinants of inlows Foreign Direct Investment (FDI) in five Asean developing countries / Muhammad Shahrul Samsuri and Mohammad Azwan Mohd Farid - Samsuri, Muhammad Shahrul; Mohd Farid, Mohammad Azwan (Faculty of Business and Management, 2019)
ASEAN economy performance has been strongly depending on the Foreign Direct Investment (FDI). FDI is known as the key source of income, business competition, capital flows, innovations and technological transfer which are important process of economic development. However, the trend of FDI inflow showed a fluctuation trend as it constant from 1995 to 2002, an increase until 2007, a drop in 2008 and 2012 and decline again starting 2015. While in 2016 and 2017 the FDI rose to a higher level. The increase is good but a matter of fact, a fluctuation shown gives the sign that FDI inflows can rose and fall at any time. Therefore, the purpose of this study to determine the factors that affecting the FDI inflows for five selected ASEAN developing countries based on the independent variables which are Gross Domestic Product (GDP), export (EXP), exchange rate (EXR), inflation (INF) and corruption (COR). The data collected annually from 1998 to 2017 by using panel series data. The data that been collected from World Bank Data. The countries that involved in this research are Indonesia, Malaysia, Thailand, Philippines and Vietnam. The data will be measured by using multiple test like Unit Root test, Pooled OLS test and Regression test. The result show that export, exchange rate and corruption shown a significant positive effect while GDP shown a significant negative effect toward FDI inflow. However, inflation show insignificant effect towards FDI inflow. This result will further the understanding of individual, policy maker, investor and economist about the important and factors affecting FDI inflow for the ASEAN developing countries.